Modeling and Execution the Control Strategy for the Three-Level Rectifier Based on Voltage Oriented Control - K. Y. Ahmed; N. Z. Yahaya; K. Ramani; V.S. Asirvadam (Institute of Advanced Engineering and Science, 2017)
In the recent years, three-level rectifier becomes an attractive rectifier replaced the two-level rectifiers. This rectifier provides many advantages, such as sinusoidal input current which contains low harmonics, unity power factor, bi-directional power flow, low voltage and switching loss for each switch. This paper presents a modelling and execution of the three-level rectifier for improvement of power quality under different loading based on voltage oriented control. The mathematical model and the control design were presented in this paper for the current inner loop and voltage outer loop, respectively. In order to evaluate the operation of the three-level rectifier under different conditions, the model was simulated by using MATLAB/Simulink. The experiment has been used to confirm the operation of the rectifier and its controller. The simulation and experimental results show that the excellent performance under steady-state and dynamic load variations was achieved; the unity power factor and pure sinusoidal in the grid side has also been accomplished.